MODEL TARIAN ANAK BERBASIS PERMAINAN TRADISIONAL JARAK-JARAK ANTUM - Riska Aprilia Harahap; Patmawati; Endah Yunita; Oktaviani Andriani; Irma Armelia Saputri; Kurniawati; Jihaan Mariza; Indah Maya Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research uses a qualitative descriptive approach, literature study method. The purpose of writing the article is to find out that traditional games can be a model for children's dance, especially for children in elementary school. The data source used is secondary data. Secondary data is obtained from library studies in various literature sources. This data collection method is known as library research. This research is based on the background that dance learning in elementary schools often faces challenges in creating learning models that are interesting and appropriate to the needs and characteristics of children, especially children in elementary schools. Dance learning is learning that teaches students to play while learning and dance also functions to help the growth of children's cognitive, affective and psychomotor development. By integrating the movements in the distance-arak antum game into dance movements, it is hoped that it can provide a learning model that can improve motor skills, creativity, interests, talents and cultural understanding in children in elementary schools. The results of the research show that the traditional long-distance game can be adapted into an innovative children's dance model. By combining game elements such as circle formation, spinning movements and a spirit of togetherness. This dance not only has a positive impact on a fun learning experience for children but also to preserve the cultural values ​​contained in traditional games.